SOSIALISASI DAN PRAKTIK ALAT KESELAMATAN DASAR DI LAUT UNTUK MENINGKATKAN PENGETAHUAN DAN KETRAMPILAN PENGUNJUNG WISATA BAHARI - Ratna Ratna; Sri Wahyuni Firman; Muh Kasim; Endang Gunaisah; Misbah Sururi; Hendra Poltak (Buletin SWIMP, 2022)
The potential contained in the sea is able to create a source of welfare for humans with the ability to manage it sustainably. However, the sea can also be a source of disaster if the management of marine resources is not known and avoids disasters at sea. Community service to provide an understanding of maritime potential and the practice of safety equipment to increase knowledge and skills for partners who visit tourist attractions. Servants carried out socialization through lectures and practices using basic safety equipment to 20 Aisyiyah partners. Observations were made to determine the partner's ability to carry out the requested practice with the result that all partners were able to use basic safety tools properly. The skills acquired by partners can be applied to activities at Sea.